The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.bjoms.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of orthognathic surgery on quality of life: a comparison between orthodontics-first and surgery-first approaches

Abstract: Aim; To compare the impact of the orthodontics-first approach (OFA) with the surgeryfirst approach (SFA), for the correction of dentofacial deformities, on quality of life, anxiety and depression. Materials and methods; Data were collected from 32 patients (aged 17-47 years), all treated through a single multidisciplinary orthognathic clinic. Patients completed a 22-item Orthognathic Quality of Life Questionnaire (OQLQ), a 7-item Generalized Anxiety Disorder (GAD-7) questionnaire and a 9-item Patient Health Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
0
20
1
4
Order By: Relevance
“…The mean values for all OQLQ domains in the total cohort of our patients with malocclusion were lower than in previously published studies (10,(29)(30)(31). The data varies because of differences in study protocols and settings.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The mean values for all OQLQ domains in the total cohort of our patients with malocclusion were lower than in previously published studies (10,(29)(30)(31). The data varies because of differences in study protocols and settings.…”
Section: Discussioncontrasting
confidence: 73%
“…Quality of life has therefore recently been assessed using OQLQ in two groups of patients with dentofacial deformities after the orthodontic-first and orthognathic-first approach in 32 patients. It was shown that the mean OQLQ score and the individual domain scores showed significant improvements at six weeks and six months post-operatively (31). The strength of our study might be in the rather high number of study participants treated and followed-up at the national referral centre.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Many patients seek dental and maxillofacial surgery not only to improve function but also for esthetic improvements in the smile or face. Therefore, orthognathic surgery has a potential impact on the quality of life, psychosocial well-being, facial esthetics, and oral function [ 1 ]. It is performed to correct dentoskeletal discrepancies and seek harmony between upper and lower jaws, improving occlusal function.…”
Section: Introduction and Importancementioning
confidence: 99%